Self-reported sexually transmitted infections among sexually active men in Ghana - Abdul-Aziz Seidu; Ebenezer Agbaglo; Louis Kobina Dadzie; Justice Kanor Tetteh; Bright Opoku Ahinkorah (BMC, 2021)
Abstract Background In sub-Saharan Africa, sexually transmitted infections (STIs) other than HIV are major public health problems. This study, therefore, sought to assess the prevalence and factors associated with self-reported STIsamong sexually active men in Ghana. Methods Data from the 2014 Ghana demographic and health survey wereused to conduct the study. This research included a total of 3051 sexually active men aged 15-59 years. Self-reported STI was the outcome variable. The data were analyzed using both descriptive (frequencies and percentages) and inferential (binary logistic regression) analysis. Results The prevalence of self-reported STIs in the past 12 months preceding the survey was 6.0% (CI:4.7-6.8). Compared to men aged 45-59 years, those aged 25-34 (aOR = 2.96, CI: 1.64-5.35), 15-24 (aOR = 2.19, CI: 1.13-4.26), and 35-44 (aOR = 2.29, CI: 1.23-4.24) were more likely to report an STI. Men who had 2 or more sexual partners apart from their spouse were more likely to report an STI compared to those with no other partner apart from spouse (aOR = 4.24, CI: 2.52-7.14). However, those who had their first sex when they were 20 years and above (AOR = 0.66, CI: 0.47-0.93) and men who read newspaper/magazine had lower odds (aOR = 0.53, CI: 0.37-0.77) of reporting STIs compared to those who had sex below 20 and those who did not read newspaper/magazine respectively. Conclusion The study has revealed a relatively low prevalence of self-reported STI among sexually active men in Ghana. Sexually active men aged 25-34 years, those whose age at first sex is below 20 years and those with two or more sexual partners apart from their spouse had higher odds of reporting STIs. However, reading a newspaper was found to be positive in reducing the odds of reporting STIs. To reduce STIs among sexually active men in Ghana, it is important for health systems and stakeholders to consider these factors and put in place measures to mitigate those that put men at risk of STIs and encourage the adoption of the protective factors. Mass media can be used as a useful avenue for encouraging men to report STIs in order to avoid transmitting them to their partners.